ETNOGRAFI KOMUNIKASI TRADISI ARAK BERARAK ADAT PERNIKAHAN PADA SUKU MELAYU DI DESA LUBUK BENDAHARA TIMUR KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU - Firdaus, Jia’an Sin; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Arak berarak is one of the ceremonies or processions contained in the traditional marriage of the Malay tribe in Lubuk Bendahara Timur Village, Rokan IV Koto District, Rokan Hulu Regency. The purpose of this study is to analyze the communicative situation, communicative events and communicative acts of the arak berarak tradition in Malay tribal weddings in Lubuk Bendahara Timur Village. The research used qualitative method. The research subjects were 7 people who were 3 traditional leaders, 1 bundo kandung, 1 bride's parents, and 2 brides who were selected using purposive technique. The results of the study show that the communicative situation of the arak berarak tradition is carried out in the yard of the bride's residence. While communicative events include a whole series of components that build communication, namely event type, topic, purpose and function, participants, message form, message content, action sequence, interaction rules and interpretation norms in the arak berarak tradition. And the communicative act is in the form of people who know and understand the implementation of the arak berarak traditio